MODEL COOPERATIVE SCRIPT BERPENDEKATAN SCIENCE, ENVIRONMENT, TECHNOLOGY, AND SOCIETY (SETS) TERHADAP HASIL BELAJAR (Jurnal Inovasi Pendidikan Kimia, 2013)
This study aimed to determine the positive effects of the applicatioan of learning model by using script cooperative with SETS approach to chemistry students' learning outcomes of student in class X. The population in this study is students class X high school in Kendal. Sampling is done by cluster purposive sampling technique, obtained one class as a experiment class that uses of script cooperative learning with the model SETS approach and another class as the gain control class with expository teaching using SETS approach. Data were collected by using documentation method, testing, observation and questionnaires. Based on the analysis of  affective domain data, it gained score percentage of 80% for the experimental class and 78% for   control class. While the score percentage for the psychomotor domain data acquired 79% of the experimental class and 78% the control class. Based on the analysis of the results, obtained correlation coefficient r b 0.52 with the contribution of 28%. The conclusions in this study is the use of script cooperative learning with the model SETS approach have an effects on the the learning outcomes of chemistry class X of high school students in Kendal on the subject redox concept with contributions of 28%.